IMPLEMENTASI PELAPORAN KEUANGAN MELALUI APLIKASI AKUNTANSIKU PADA ORGANISASI NIRLABA SMP ISLAM TERPADU BINA UMMAH KABUPATEN CIREBON - Ahdi, Makmuri; Nakhwatunnisa, Haulah; Wahyuningsih, Nining; Iqbal, Mohammad (Universitas Esa Unggul, 2023)
This community service activity was carried out because there are still many non-profit organizations that do not produce Financial Statements by ISAK 35. This activity aims to train and implement the Akuntansiku application for making non-profit financial reports at SMPIT Bina Ummah. The methods used in this research include lectures, discussions, and the practice of preparing financial reports. The time for carrying out community service activities is 4 (four) months from July to October 2022. This activity begins with program socialization, basic accounting training, training on the Akuntansiku application, and training on preparing vouchers, which consist of cash receipt vouchers, vouchers cash disbursements, bank receipt vouchers, bank disbursement vouchers, and memorial journal vouchers. Nonprofit financial statements are essential to inform the statement of financial position. In addition, financial reports are used as a basis for decision-making, so accountability is needed in preparing financial reports. One application that can be used for making financial reports is the Akuntansiku application. With this service program, it is hoped that SMPIT Bina Ummah can make non-profit financial reports according to ISAK 35 using the Akuntansiku application.